Misery of living with parthenium dermatitis: Correlation between clinical severity and quality of life - Shail Agarwal; Shivani Saini; Ramesh Kumar; Atul Vijay (Wolters Kluwer Medknow Publications, 2021)
Background: Parthenium dermatitis is caused by friable plant extracts of Parthenium hysterophorus and related species. Approximately 40% of cases of plant dermatitis in India are contributed by this single species. Materials and Methods: This was a cross-sectional, observational study conducted in the Department of Dermatology of Jhalawar Medical College. Ninety-nine consecutive patch test positive parthenium dermatitis human subjects of age more than 16 and either sex were included. The study period was 11 months between September 2019 and August 2020. Sociodemographic, clinical profile parthenium dermatitis severity score (PDSS) and Dermatology life quality index (DLQI) were obtained from each patient. Correlation between PDSS and DLQI was obtained using Pearson's two-tailed coefficients. Results: Our study included 62 men and 37 women (1.67:1). The mean age was 51 ± 10.27 years. Mean duration of disease was 8.47 ± 4.45 years, and mean PDSS was 57.25 ± 17.65, mean DLQI was 17.14 ± 5.56. ABCD with CAD was the most common clinical subtype (45.45%). A significant positive correlation was observed between PDSS and DLQI. Conclusion: In this study, a significant impairment in quality of life (QoL) was observed in patients with higher score of PDSS and increasing duration, emphasizing that the disease needs specialized care including multiple indoor admission at the time of flare-up of disease.